Experimental Characterisation and Modelling of Sustainable Multiscaled Bionanocomposites - Mousa, Mohanad Hashim (Curtin University, 2018)
Novel polyvinyl (PVA) bionanocomposite films reinforced with four different types of nanofillers were manufactured based on a solution casting method. The effect of nanofiller size, shape and content on the material performance of bionanocomposites was holistically investigated in experimental characterisation. Furthermore, nanomechanical properties and dimensions of nanointerphases in PVA bionanocomposites were systematically determined via peak force quantitative nanomechanical tapping mode (PFQNM). Finally, newly developed micromechanical modelling results confirmed good agreement with experimental data.